Indications for blood and blood products transfusions among children in a semi-urban tertiary hospital in Nigeria - SO Akodu (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Anaemia is prevalent among children in our environment, often necessitating blood transfusions. The knowledge of the common indications for blood transfusion and the required preventive measures is likely to reduce the transfusion rates. Objective: To determine the disease conditions requiring blood transfusion in post-neonatal age children at the Olabisi Onabanjo University Teaching Hospital, Sagamu, Nigeria. Methods: The hospital records of all children aged 1 month to 18 years admitted into the post-neonatal ward who received blood transfusions over 18 months (1st July 2015to31st December 2016) were reviewed. Results: There were 710 paediatric admissions out of which 82 (11.6%) received blood transfusions. Ninety transfusions were carried out amongst 82 children, at a ratio of 1.1 transfusions per child. Severe malaria (28.1%), sickle cell anaemia (19.5%) and septicaemia (18.3) were the most common disease conditions requiring blood transfusions. The leading blood products transfused included packed red cells (64.5%) and whole blood (30.0%). Conclusion: Blood transfusion is frequently indicated in the paediatric population in our setting, largely due to severe malaria and sickle cell anaemia problems. Intensifying efforts on the use of long-lasting insecticide-treated nets and environmental control may reduce the prevalence of severe malaria, while improved nutrition, adequate hydration, regular malaria prophylaxis, prompt treatment of infections and regular use of haematinics may minimize the need for blood transfusions among children with sickle cell anaemia.